2017
DOI: 10.1680/jmacr.17.00026
|View full text |Cite
|
Sign up to set email alerts
|

Cracking in walls with combined base and end restraint

Abstract: Restraint of early-age thermal and long-term shrinkage strain can cause cracking in reinforced concrete members. Eurocode 2 provides guidance on the design of crack control reinforcement in reinforced concrete elements with base (edge) and end restraint but not combined base and end restraint which commonly occurs. The paper describes an experimental programme, which was conducted to investigate early-age and long-term shrinkage cracking in reinforced concrete walls with combined base and end restraint. The ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…An example of a situation where both forms of restraint may exist can be found by considering a new section of concrete cast between two pre-existing concrete wall sections and onto a pre-existing concrete base [9]. Whilst a greater understanding of edge restraint in isolation is being gained [10,11], the optimum problem constituted by a combination of the two restraints is still little understood. Forth [12] suggested that in such a scenario, both types of restraint will dominate in different parts of the wall.…”
Section: Introductionmentioning
confidence: 99%
“…An example of a situation where both forms of restraint may exist can be found by considering a new section of concrete cast between two pre-existing concrete wall sections and onto a pre-existing concrete base [9]. Whilst a greater understanding of edge restraint in isolation is being gained [10,11], the optimum problem constituted by a combination of the two restraints is still little understood. Forth [12] suggested that in such a scenario, both types of restraint will dominate in different parts of the wall.…”
Section: Introductionmentioning
confidence: 99%